2014
DOI: 10.1016/j.marpetgeo.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Gas hydrate destabilization and methane release events in the Krishna–Godavari Basin, Bay of Bengal

Abstract: Methane release events have been linked to global warming, alteration of the carbon cycle and influence on biota. However, unequivocal evidence of paleomethane release events are limited. We report several negative carbon stable isotope excursions in planktic and benthic foraminifera in a core (MD161-8) from the Krishna-Godavari (K-G) Basin, Bay of Bengal. The most negative δ 13 C spikes are recorded during the marine isotope stages MIS-4 and at the transition of MIS-5 to 4. Occurrence of highly 13 C depleted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…The δ 13 C TIC reported here is partially influenced by the presence of foraminifera with the calcareous test having δ 13 C value ranging from −1 to +1‰ [ Joshi et al ., ] and pure authigenic carbonates resulting from AOM could have been even more 13 C depleted. The δ 34 S CRS profile shows significant depletion in 34 S within the depth zone of 13–16 mbsf.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The δ 13 C TIC reported here is partially influenced by the presence of foraminifera with the calcareous test having δ 13 C value ranging from −1 to +1‰ [ Joshi et al ., ] and pure authigenic carbonates resulting from AOM could have been even more 13 C depleted. The δ 34 S CRS profile shows significant depletion in 34 S within the depth zone of 13–16 mbsf.…”
Section: Discussionmentioning
confidence: 97%
“…Approximately 6& down core enrichment in carbon isotope ratio of methane observed below SMTZ may be attributed to the continued preferential removal of the isotopically lighter molecules from the carbon pool (CO 2 ) during methanogenesis resulting in a progressive shift in the residual substrate toward enriched stable carbon isotope ratios following Rayleigh fractionation [Whiticar, 1999]. Mazumdar et al [2012aMazumdar et al [ , 2014b reported down core (below SMTZ) increase in residual d 13 C CH4 values ranging from 3 to 19& from K-G and Mahanadi basin cores. Much greater enrichment is expected at greater depths .…”
Section: Methanogenesismentioning
confidence: 96%
“…δ 13 C CH4 values (−60 to −85.5‰) suggest a possible biogenic origin of methane at the studied location [ Mazumdar et al , 2009]. The δ 13 C TIC reported here is partially influenced by the presence of foraminifera with the calcareous test having δ 13 C value ranging from −1 to +1‰ [ Joshi and Mazumdar , 2011; Joshi et al, manuscript in preparation, 2012]. High TIC contents (Figures 2c and 3c) corresponding in depth to the depleted carbon isotope ratios suggest the accumulation of authigenic carbonate in the sediment.…”
Section: Discussionmentioning
confidence: 99%
“…2) is representative of the Godavari continental slope (Mazumdar et al, 2009;Ramprasad et al, 2011;Joshi et al, 2014) and is driven by changes in the siliciclastic sedimentation rate as dilution by biogenic carbonates is less than 5 % ). Despite a lower sea level at the time, the flux was relatively small in the early Holocene (∼ 25 g cm −2 kyr −1 ) but began to increase after 6000 years ago (∼ 40 g cm −2 kyr −1 ), as soon as the monsoon started to decline but well before the adoption of Neolithic agriculture and settlement of the savannah zone of the central peninsula (∼ 4500 years ago; Fuller, 2011).…”
Section: Erosion In the Godavari Basinmentioning
confidence: 99%